Given the following table, find the rate of change between f(-2) and f(0). Average rate of change =
x -3 -2 -1 0 1
f(x) -13 -11 -7 -1 17.

5
-5
-1/5
1/5

Respuesta :

[tex] \bf \begin{array}{l|rrrrr}
x&-3&\boxed{-2}&-1&\boxed{0}&1\\\\
f(x)&-13&\boxed{-11}&-7&\boxed{-1}&17
\end{array}\\\\
-------------------------------\\\\
slope = m = \cfrac{rise}{run} \implies
\cfrac{ f(x_2) - f(x_1)}{ x_2 - x_1}\impliedby
\begin{array}{llll}
average~rate\\
of~change
\end{array}\\\\
-------------------------------\\\\
\begin{cases}
x_1=-2\\
x_2=0
\end{cases}\implies \cfrac{f(0)-f(-2)}{0-(-2)}\implies \cfrac{(-1)~~-~~(-11)}{0+2}
\\\\\\
\cfrac{-1+11}{2}\implies \cfrac{10}{2}\implies 5 [/tex]

Answer:

Average rate of change =5